THE ESSENCE OF MANAGEMENT AS AN ART (Neo Science Peer Reviewed Journal, 2023)
The article analyzes such issues as New Uzbekistan, the level of etiquette in the management process of young people, its development, its specific characteristics and conditions, the national-historical way of life and thinking of the population, folk traditions and customs.